Adsorption of VOCs onto engineered carbon materials: A review - Zhang, Xueyang; Gao, Bin; Creamer, Anne Elise; Cao, Chengcheng; Li, Yuncong (Journal of hazardous materials, 2017)
[Display omitted] Volatile organic compounds (VOCs) severely threaten human health and the ecological environment because most of them are toxic, mutagenic, and carcinogenic. The persistent increase of VOCs together with the stringent regulations make the reduction of VOC emissions more imperative. Up to now, numerous VOC treatment technologies have emerged, such as incineration, condensation, biological degradation, absorption, adsorption, and catalysis oxidation et al. Among them, the adsorption technology has been recognized as an efficient and economical control strategy because it has the potential to recover and reuse both adsorbent and adsorbate. Due to their large specific surface area, rich porous structure, and high adsorption capacity, carbonaceous adsorbents are widely used in gas purification, especially with respect to VOC treatment and recovery. This review discusses recent research developments of VOC adsorption onto a variety of engineered carbonaceous adsorbents, including activated carbon, biochar, activated carbon fiber, carbon nanotube, graphene and its derivatives, carbon-silica composites, ordered mesoporous carbon, etc. The key factors influence the VOC adsorption are analyzed with focuses on the physiochemical characters of adsorbents, properties of adsorbates as well as the adsorption conditions. In addition, the sources, health effect, and abatement methods of VOCs are also described.